Determinants of the duration of European appellate court proceedings in cartel cases - Florian Smuda; Patrice Bougette; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
The duration of appellate court proceedings is an important determinant of the efficiency of a court system. We use data of 234 firm groups that participated in 63 cartels convicted by the European Commission between 2000 and 2012 to investigate the determinants of the duration of the subsequent one- or two-stage appeals process. We find that while the speed of the firststage appellate court decision depends on the court's appeals-related workload, the complexity of the case, the degree of cooperation by the firms involved and the clarity of the applied rules and regulations, the second-stage appellate court proceedings appear to be largely unaffected by those drivers. We take our empirical results to derive conclusions for both firms that plan to file an appeal as well as public policy makers.
urn:nbn:de:bsz:180-madoc-370776
Keywords: K21; K41; K42; L41; 330; Law and economics; antitrust policy; cartels; appeals; European Union